Effect of N-doped carbon layer on Co3O4 nanowire-graphene composites as anode materials for lithium ion batteries. (January 2019) - Kim, Yoongon; Noh, Yuseong; Han, Hyunsu; Bae, Jaejin; Park, Sungmin; Lee, Seungjun; Yoon, Wongeun; Kim, Ye Kyu; Ahn, Hyunwoo; Ham, Moon-Ho; Kim, Won Bae
Abstract: In this paper, an anode material system of Co3 O4 nanowires composited with reduced graphene oxide (Co3 O4 NWs/rGO) and protected by N-doped carbon layer (Co3 O4 NWs/rGO@NC) was prepared for lithium ion batteries. The N-doped carbon layer could serve as stress relief matter to reduce volume changes of the Co3 O4 NWs/rGO during repeated charge/discharge cycles, and also enhance the reaction kinetics as a highly conductive layer between the Co3 O4 NWs and electrolyte. The Co3 O4 NWs/rGO@NC electrode delivered a high discharge capacity of ca. 995 mAh g −1 at 0.1 C after 65 cycles, and showed a much better rate performance of 428 mAh g −1 even at a high current rate of 5 C as compared to those of Co3 O4 NWs/rGO electrode (203 mAh g −1 ). The demonstrated electrochemical properties suggested that the N-doped carbon coating on the composite of Co3 O4 NWs and rGO could significantly enhance the durability and rate capability of the anode material for high performance lithium ion batteries. Highlights: Nitrogen atoms were reacted with defects of carbon material and doped in the lattice. N-doped carbon layer enhances the reaction kinetics between the Co3 O4 NWs and electrolyte. N-doped carbon coating could significantly enhance the durability and rate capability.